Pengendalian Internal Pemberian Kredit Mikro UMKM Untuk Menjaga Likuiditas Dimasa Pandemic Covid-19 Pada Bank BPR Serang Cabang Cinangka - Adih Supriadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this paper is to answer how the internal control in the provision of MSME microcredit by the BPR Serang Bank Cinangka Branch during the Covid-19 Pandemic and find out how the liquidity is. The writing method used is descriptive qualitative, while the population used is the financial statements of BPR Serang Cinangka Branch with a sample of 2019-2020. The results of the discussion showed that the internal control in providing microcredit to MSMEs by Bank BPR Serang Cinangka Branch during the Covid-19 period were customer interviews, OTS, SLIK checking, curriculum vitae, and the application of 5C principles (character, capacity, capital, colleateral, and condition). Meanwhile, the liquidity of Bank BPR Serang Cinangka Branch during the Covid-19 period based on the results of the calculation of the Quick Ratio of BPR Serang Cinangka branch in 2019-2020 illiquid conditions of its current assets, based on the LAR ratio in 2019 healthy conditions and in 2020 unhealthy conditions or unable to meet demand for credit from assets owned or assets, based on LDR ratio in 2019-2020 very healthy condition, based on NPL ratio in 2019 NPL below 5% means healthy condition but in 2020 NPL above 5% means less healthy, because based on the amount of NPL, a bank that is in a healthy category must have an NPL below 5%.